Pengujian White Box pada Aplikasi Cash Flow Berbasis Android Menggunakan Teknik Basis Path - Citra Teguh Pratala; Ebenhaezer Mahardhika Asyer; Ima Prayudi; Aries Saifudin (Teknik Informatika Universitas Pamulang, 2020)
An application that has poor quality and defects not only causing additional time of software development process but also can deliver disadvantage to the users of the application. Every application will not be separated from the testing process. The testing process aims to find out errors in the software. One of the methods used is white box testing. White box testing is a testing method at the level of the software flow. To find out whether the Cash Flow application does not have an error it will be tested with a base path technique that starts from making a Flow Graph, Cyclomatic Complexity (CC) and doing a Case unit. The implementation of the white box testing method using the Base path technique in the cash flow application can evaluate the complexity of the program flow and while conducting unit tests it can determine the number of test scenarios to be performed. After doing Cash Flow application testing with no errors, thus all tests were successful. The results of this test can be used as a reference to improve the application as expected.